Body Shaming Dan Dampaknya Pada Rasa Percaya Diri Mahasiswa Tadris Bahasa Inggris - Tri Intan Febriany; Septi Gumiandari (Pusat Riset dan Inovasi Nasional, 2024)
Many people, including young people, often experience insecurity and shame about their own body shape. This is because the perpetrator of body shaming can unconsciously harm the victim's psychological development, including self-confidence. This research aims to explain the forms of body shaming and their impact on a person's self-confidence. The method used in this research is qualitative. Researchers collected data using interview techniques and took data from the personal experiences of Tadris English students. The results of this research are that there are various forms of body shaming and do not have a positive impact on the victim. Body shaming has a major impact on reducing the victim's self-confidence. Perpetrators of body shaming are not only friends, even their closest family also do it.